2011
DOI: 10.1002/ccd.23080
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anticoagulation on ionic and nonionic contrast media effect on thrombogenesis and fibrinolysis: The PEPCIT study

Abstract: The prothrombogenic effect of iodixanol is related primarily to an increase in fibrin stiffness with subsequent delayed fibrinolysis, something not seen with ioxaglate. Anticoagulation does not appear to have any impact on this fibrin clot abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
4
6
1
Order By: Relevance
“…Opacity of hydrogels by addition of the iodixanol that is contained in Visipaque has recently been tested in chitosan hydrogels for controlled blood vessel embolization (Fatimi et al, 2016). Iodixanol extends blood-clotting time (Bellemain-Appaix et al, 2012), which is concurrent with the results obtained here using a fibrin sealant. It is a non-ionic dimer (Jones and Goodall, 2003).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Opacity of hydrogels by addition of the iodixanol that is contained in Visipaque has recently been tested in chitosan hydrogels for controlled blood vessel embolization (Fatimi et al, 2016). Iodixanol extends blood-clotting time (Bellemain-Appaix et al, 2012), which is concurrent with the results obtained here using a fibrin sealant. It is a non-ionic dimer (Jones and Goodall, 2003).…”
Section: Discussionsupporting
confidence: 87%
“…This is in line with previous studies showing reduction of chitosan hydrogel swelling by increasing their iodixanol concentration (Fatimi et al, 2016). The addition of iodixanol to fibrin-rich clots resulted in shorter, thinner, and more numerous fibrin fibers when compared to counterparts made with ioxaglate or buffer, leading to a much more compact 3D architecture with smaller pores and higher crosslinking of fibrin fibers (Bellemain-Appaix et al, 2012). Furthermore, there was an apparent negative swelling after 5 min with the test hydrogel under the current conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This in vitro study demonstrated an additive inhibitory effect with ioxaglate in the setting of heparin and glycoprotein IIb/IIIa inhibitor, such that ioxaglate completely abolished thrombin generation, while iodixanol slowed clotting time but had no effect on the amount of thrombin formed . Furthermore, only one prior study evaluated the effect of CM and bivalirudin on blood samples derived from patients with severe coronary artery disease on dual anti‐platelet therapy . Similar to prior experimental studies, in vitro addition of ioxaglate demonstrated a more favorable profile on coagulation parameters than iodixanol, but these differential effects did not change with the addition of bivalirudin .…”
Section: Discussionsupporting
confidence: 63%
“…Advances in pharmacology have led to classes of agents targeted at one of the three main components of the thrombotic process: thrombin, fibrin, and platelets. Contrast media (CM) has been shown in animal models and in vitro experiments to have variable effects on each of these three components . These data suggest that ionic CM may have greater antithrombotic properties than non‐ionic CM, at the expense of higher osmolality and fluid retention.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have suggested that ionic low-osmolar contrast is less thrombogenic compared to either isosmolar or low-osmolar nonionic contrast [24]. Clinical trials evaluating potential thrombotic complications have focused on MACE (cardiac death, recurrent nonfatal acute MI, and emergency CABG or repeat PCI) or acute and subacute stent restenosis [25, 26].…”
Section: Other Acute Endpointsmentioning
confidence: 99%